The Effect of Work-Life Balance and Leadership Style on Employee Turnover Intention Through Job Satisfaction as An Intervening Variable - Intan Masito; Siti Safaria (Winter Journal: IMWI Student Research Journal, 2026)
This study aims to determine the effect of work-life balance and leadership style on turnover intention through job satisfaction as an intervening variable. The case study for this research was conducted at PT. Permodalan Nasional Madani, Jember Branch. The basis for this study is the issue of turnover intention, or the desire of employees to leave the company, which is one of the challenges currently faced by PT. Permodalan Nasional Madani, Jember Branch. As we know, a high number of turnover intentions greatly affects the development of the company's business. The data used in this study were obtained from 391 employees who filled out a questionnaire provided by the researcher, with a deadline of 5 days. The results of this study indicate that a good work-life balance improves job satisfaction. However, even with a good work-life balance, turnover intention cannot be reduced. High job satisfaction can reduce turnover intention. A good leadership style improves job satisfaction. However, even with a good leadership style, turnover intention cannot be reduced. Job satisfaction mediates work-life balance in reducing turnover intention. Job satisfaction also mediates leadership style in reducing turnover intention.